Coping with the crisis: challenges to migrant entrepreneurship in Athens at a time of recession and austerity - Χατζηπροκοπίου Πάνος; Φραγκόπουλος Γιάννης (The Greek Review of Social Research, 2016)
This paper draws on fieldwork research that took place during 2012-13 in order to assess the circumstances of migrant entrepreneurship in the years of the crisis and the ways self-employed immigrants develop in order to cope with the situation they are faced with. The study builds a comparative perspective between migrant-owned and native-owned small businesses in three neighbourhoods of central Athens. Through these, the study unveils three parallel “crises” that predated the current one, even if they are now mingled with its overwhelming dynamics. Firstly, Greece’s «immigration crisis», a product of the way migratory trends have been managed by the State since the early 1990s. This partly relates to the «crisis of small enterprises», major employers of migrant labour in the 1990s, and the challenges posed by internationalisation and large-scale competition. Both are in turn associated to the «urban crisis» of Athens, referring to processes of urban development in relation to shifting social and economic geographies in the city.